Yield and Yield Components of Wheat as Influenced by Sowing Date and Humic Acid (International Journal of Natural Sciences, 2016)
In order to investigate the effect of seed sowing date and humic acid foliar application on some agronomic traits of bread wheat an experiment was conducted in Islamshahr, Iran during 2013 growing season. The experimental design was a complete randomized block design arranged in factorial with three replications. The first factor was included two sowing date (middle of November and middle of December) and the second factor was included three humic acid levels (0, 4 and 8 liter ha-1). The results indicated that late seed sowing lead to significant reduction in agronomic traits such as tiller number, spike number, seed number and seed weight. In addition, vegetative growth was affected by late seed sowing and so that shorter plants were observed. Number of days until spike emergence, number of days until pollination and number of days until physiological maturity decreased due to late seed sowing. By contrast, humic acid application increased plant growth and improved yield and yield components through extending growing period.International Journal of Natural Sciences (2015), 5(1) 8-14